Pengaruh Kemandirian Belajar dan Berpikir Kritis Terhadap Hasil Belajar Matematika Siswa - Lestari, Putri Bunga Citra; Ketut Sarjana; Dwi Novitasari; Nyoman Sridana (FKIP Universitas Mataram, 2024)
This study aims to determine how learning independence and critical thinking influence the mathematics learning outcomes of grade 8th students at SMP Negeri 1 Mataram in academic year 2023/2024. This research is a quantitative with a research approach with an ex-post facto method. The population of this research was 402 students in grade 8th at SMP Negeri 1 Mataram. The sample size was 75 students who were determined using cluster random sampling techniques. The instruments in this research used an learning independence questionnaire, an critical thinking questionnaire, and a mathematics learning outcomes test in the form of essay questions. Data was analyzed using linear regression analysis it was found that there is a joint positive and significant relation between learning independence and critical thinking on the mathematics learning outcomes of grade 8th at at SMP Negeri 1 Mataram in academic year 2023/2024 with the regression equation. The correlation coefficient value is 0,875, that means to have a strong influence and contribution to learning outcomes is 76,5%.